Microwave-assisted Synthesis, Molecular Docking Study of Spirofused Heterocycles as Anti-microbial and Anthelmintic Potential - Das, Rina; Mehta, Dinesh K.; Gupta, Sumeet; Mujwar, Somdutt; Sharma, Vishal; Goyal, Anju; Patel, Samir; Patel, Archita (Letters in Organic Chemistry, 2023)
Introduction: The stereochemical characteristics of spirofused and their derivatives have recently attracted a great deal of interest in synthetic organic chemistry. Methods: A series of ecologically acceptable spirofused heterocycle compounds S(K1–K8) were made using a one- pot microwave irradiation and were characterized by FTIR, /sup>1HNMR, and Mass Spectroscopy. The Iodine-catalyzed Biginelli-type condensation process has been used to synthesize novel anti-microbial and anthelmintic potential spiroketals (spirofused) derivatives by using a fast, safe & effective microwave irradiation approach in order to get the product in maximum yield with lesser time consumption. Results: The compounds SK4 and SK5 showed promising antimicrobial activity against all bacterial (Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli) and fungal strains (Candida albicans and Aspergillus niger) with MIC 6.25 μg/mL and 12.5 μg/mL. Furthermore, molecular docking studies were also simulated for compounds SK4 and SK5 to predict the specific binding mode of these compounds. Conclusion: Albendazole (Alb) was used as a reference medicine to test the anthelmintic activity of Indian adult earthworms Eisenia fetida. Compound SK4 has been found to be an effective pharmacophore.
Keywords: spiroketal